The Simpsons treehouse of horror - Groening, Matt; Castellaneta, Dan; Kavner, Julie; Cartwright, Nancy, 1959-; Smith, Yeardley; Azaria, Hank, 1964-; Shearer, Harry, 1943-; Gracie Films; Twentieth Century-Fox Television, Inc.; Film Roman (Firm); Twentieth Century Fox Home Entertainment, Inc.; Copyright Collection (Library of Congress) (Beverly Hills, California : Twentieth Century Fox Home Entertainment, Inc., 2003)
Four tales of Simpsons horror.
Treehouse of horror XII. Hex and the city ; House of whacks ; Wiz kids.
Full screen (1.33:1).
Episodes originally broadcast on FOX in 1994-1996 and 2001.
Collective title from container.
Special features: featurette with Kang and Kodos.
Sources used: videodisc container; Copyright catalog online; Amazon WWW site, viewed October 6, 2016; Internet movie database WWW site, viewed October 6, 2016; Wikipedia WWW site, viewed October 6, 2016.
Voices: Dan Castellaneta, Julie Kavner, Nancy Cartwright, Yeardley Smith, Hank Azaria, Harry Shearer.
Keywords: Simpson, Bart -- (Fictitious character) -- Drama; Simpsons (Fictitious characters) -- Drama; Simpson, Homer (Fictitious character) -- Drama; Springfield (Imaginary place) -- Drama; Dysfunctional families -- Drama; Families -- Drama; Halloween -- Drama; Animated television programs; Horror television programs; Fiction television programs; Video recordings for the hearing impaired